Dealing with Demons: Life of Someone Suffering from Body Shame - Generose Billano; Christian Angelo Aguilar; R-jay Kevin Lim; Nicole Mendoza; Darelle Faye Sebellino; Norhata Panday (Universitas Pendidikan Indonesia (UPI), 2023)
People of all ages, genders, socioeconomic conditions, origins, and races are impacted by the significant issue of body shaming. Overall appearance, social images (appearance-cued stereotyping, social implications of appearance stereotyping), developmental consequences of appearance for psychological adjustment, and body-self interactions may all be affected. This research looks at the lives of students who have been victims of body shaming; how it affects the victims' lives and well-being; the sorts of care they need; their everyday experiences in terms of education and their surroundings; and how to assist them in building a new positive outlook on life. The diverse statements and experiences of the five (5) students from Sultan Kudarat State University Laboratory High School who were purposefully selected and interviewed through Google Meet were analyzed using a qualitative case study approach. The study's participants go about their regular lives, absorbing every bit of criticism they encounter into their motivation and inspiration. Finally, the victims have not overlooked the need for life preservation and are aware of it. Many of them make every effort to realize them, even if it means putting their emotions on the line. As this research emphasizes the value of everyone’s life, it allows us to have a deeper understanding of students who are suffering from personal issues. Despite all that has occurred to them, they remain hopeful and prepared to take chances to achieve their objectives. As a result, it is recommended that the community learn more about body shaming.